Circularly-polarized capacitively-fed UHF-RFID antenna with truncated reverse-arc shape - Boonying, Komkris; Phongcharoenpanich, Chuwong (My University, 2015)
This article presents a circularly polarized (CP) flat antenna with truncated corners using the capacitively coupled feed technique for UHF RFID applications. A radiating plate, an air gap and a ground plane constitute the antenna. The reverse-arc shape truncated corners are utilized to generate a CP radiation and the suspended structure antenna using the capacitively coupled feed technique is adopted to enhance bandwidth. A prototype antenna was fabricated and its measured results were 13% for the bandwidth and 11.54% for the 3-dB axial ratio (AR) bandwidth. The half-power beamwidths of the left hand circular polarization on x-y and x-z planes were both greater than. The measured gain on the UHF RFID system was greater than 5.90 dBic.
Keywords: annular-ring slot; capacitively coupled feed; circularly polarized; truncated corners; UHF RFID